EFFECT OF SCRABBLE GAME ON SECONDARY SCHOOL STUDENTS’ ACADEMIC ACHIEVEMENTS IN SELECTED ENGLISH LANGUAGE CONCEPTS IN ILORIN METROPOLIS - Temitayo Omolara Onasanya; Gboyega Ayodeji Aladesusi; Samuel Adenubi Onasanya (Indonesian Journal of Learning and Instruction, 2021)
This study examined the effect of scrabble game on secondary school students’ academic achievement in selected English language concepts in Ilorin metropolis. The study determined the differences in the academic achievement of students taught English language with scrabble game as well as the differences in the academic achievement of students taught English language with scrabble game based on gender among others. The study adopted a quantitative research design of an experimental and survey methods. Various statistical tools such as descriptive and inferential statistics were employed to answer the research question and test the hypotheses respectively. The results of the findings indicated that: (1) students performed well when taught English vocabulary with digital Scrabble game, (2) gender differences do not exist in using digital scrabble game to teach English vocabulary in Ilorin metropolis also Students have positive reaction to learning English vocabulary with the use of digital Scrabble game. The implication of the findings is that, engagement-based approach like Scrabble game can serves as an alternative approach to engage English language learners in the classroom. Thus, improving students academic achievement and retention. It was therefore recommended that, Scrabble game adoption should be encouraged among teachers and students. Keywords: attitude; gender; scramble game.